BETAL MACHRAILOVICH PSHUNOKOV. MATERIALS FOR CREATIVE BIOGRAPHY - I. A. KAZHAROVA (Кавказология)
The article presents the facts of the creative biography of the famous worker of culture of the Kabardino-Balkar Republic Pshunokov Betal Machrailovich. Literary works Pshunokov Betal has not yet become the object of attention of researchers. The relevance of such work is justified by the fact that without attention to his literary heritage, the picture of the work of the well-known composer in the Republic will be incomplete, and another gap may form in the history of Kabardian literature. Image Pshunokov Betal interesting for the history of Kabardian literature that to some extent continues the creative endeavors of his father, a well-known figure of the 1930-ies Machrail Tlikeshevich Pshunokov, educator, standing at the foundations of Soviet Kabardian literature, and the innocent victim in the years of political repression. Our work presents a brief overview of literary creativity Pshunokov Betal. His lyrical works, song poetry, drama and journalism are briefly characterized. Special attention is paid to his manuscript heritage, especially his memoirs. Fragments of memories are published for the first time.